Alterations of the gut microbiota and short chain fatty acids in necrotizing enterocolitis and food protein-induced allergic protocolitis infants: A prospective cohort study - Xiong, Jing; Liao, Xing-Sheng; Yin, Tong; Liu, Xiao-Chen; Bao, Lei; Li, Lu-Quan (Frontiers in Cellular and Infection Microbiology, 2022)
Background Even though presenting with similar clinical manifestations, necrotizing enterocolitis (NEC) and food protein-induced allergic protocolitis (FPIAP) have completely different treatments and prognosis. Our study aimed to quantify and evaluate differences in gut microbiota and short chain fatty acids (SCFAs) between infants with NEC and FPIAP to better identify these two diseases in clinical settings. Methods A total of 43 infants with NEC or FPIAP in Children’s Hospital of Chongqing Medical University, China between December 2020 and December 2021 were enrolled. Stool samples were prospectively collected and froze. Infants defined as NEC were those who presented with clinical courses consistent with NEC and whose radiographs fulfilled criteria for Bell’s stage 2 or 3 NEC, while those who were healthy in appearance and had blood in the stool (visible or may be microscopic), had normal bowel sounds in physical examination, were resolved after eliminating the causative food, and/or had recurrence of symptoms after oral food challenge (OFC) were defined as FPIAP. Primers specific for bacterial 16S rRNA genes were used to amplify and pyrosequence fecal DNA from stool samples. Gas chromatography-mass spectrometry (GC-MS) technology was used to determine the concentrations of SCFAs. Results Among the 43 infants, 22 were diagnosed with NEC and 21 were diagnosed with FPIAP. The microbial community structure in NEC infant stools differed significantly from those in FPIAP infant stools. NEC infants had significantly higher proportion of Actinobacteria and reduced proportion of Bacteroidetes compared with FPIAP infants, and the proportions of Halomonas, Acinetobacter, Bifidobacterium, and Stenotrophomonas in NEC infants were significantly higher than that of FPIAP infants. In addition, infants with NEC had significantly lower levels of acetic acid, propionic acid, butyric acid, isovaleric acid, and total SCFAs, and higher level of hexanoic acid as compared to the infants of the FPIAP group. Conclusions The differences of gut microbiota composition and concentrations of SCFAs might represent suitable biomarker targets for early identification of NEC and FPIAP.